Synoptic analysis of the most severe flood in Karkheh basin (Flood 1 April 2019) - dana rahimi; Javad khoshhal dastjerdi; Dariush rahimi (تحقیقات کاربردی علوم جغرافیایی)
Among natural disasters, floods have the highest human toll. The economic impacts of floods are greater in developing countries, including Iran, and are particularly severe in the colder months of the year in the west of the country. The purpose of the present study is to analyze the most severe historical synoptic floods that occurred in Karkheh Basin  (1 April, 2019). Descriptive - analytical research method and its environmental approach into circulation. Analysis of synoptic systems of large floods such as the April 12, 2019 floods show that Western Europe's high-pressure systems, Black sea, East of the Caspian and low pressure north of the Red Sea, Eastern Mediterranean in harmony with the high-rise systems of Western Europe, Low Mediterranean East with a temperature drop of about 50 degrees Celsius(The temperature at sea level In the eastern Mediterranean and Red Sea about 25 degrees Celsius and in the middle of the atmosphere -25 degrees Celsius) also the climb Humidity from the Arabian Sea, North Indian Ocean, Red Sea, Oman Sea and Persian Gulf and Along with Mid-width cold air loss On the area and the establishment of the Polar jet stream) Core up to 70 m(And the establishment of the front jet stream And positive rotation area On the area shows the structure of the synoptic systems causing the flood in the area.